PENGARUH SIKAP KELUARGA TERHADAP PENCEGAHAN KOMPLIKASI HIPERTENSI GAREDE II SEBELUM DAN SESUDAH DILAKUKAN PENDIDIKAN KESEHATAN - karyawanto karyawanto; Annisa Agata; Afrizal Al Arif (Universitas Mitra Indonesia, 2021)
Improving the attitude of the family in the task of health maintenance in order to be able to take good care of yourself and family members so as to improve the quality of life and prevent further complications of the disease can be done with counseling. The purpose of the study was to find out the influence of family attitudes on the prevention of grade II hypertension before and after health education in the working area of Kibang Budi Jaya Health Center, Lambu Kibang District, Tulang Bawang Barat Regency. This type of research is quantitative with One Group's quasi-experimental approach to pre-test and post-test design. The population is a family member of people with hypertension in Kibang Budi Jaya District Lambu Kibang West Onion Regency as many as 413 people and a sample of 203 people. Data analysis uses statistical tests of dependent t tests. Pre-test group and post-test design.The population is a family member of people with hypertension in Kibang Budi Jaya District Lambu Kibang West Onion Regency as many as 413 people and a sample of 203 people. Data analysis uses statistical tests of dependent t tests. The results showed that there was an influence on family attitudes towards the prevention of hypertension grade complications before and after Health Education in the Kibang Budi work area. Puskesmas Jaya, Lambu Kibang District, Tulang Bawang Regency with a value of p = 0,000.The advice, for puskesmas is expected to implement effective counseling is to increase frequency counseling by making regular schedules, the use of interesting props (demonstrations) when counseling such as food / beverage sample pantomimes is the concern of respondents in receiving counseling materials, good audio visual facilities and homogeneous extension of participants so as not to hinder the reception of information. So it will have an impact on the change in family attitude towards the prevention of hypertension complications.